Islamic Literature on Social Media: Changes in Style, Meaning, and Function - Sholihah, Roudlotus; Kusumawardani, Indah Dian; Fajriyah, Nindya Nisfiatul; Nurmaulidiva, Violentia Wahyu (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Differences in access and ability to use digital technology—shaped by the dominance of social media—have had a significant impact on the development of Islamic literature, in terms of aesthetics, meaning, and modes of communication. This study aims to examine the changes in style, meaning, and function of Islamic literature as it evolves across various social media platforms by applying a qualitative approach and content analysis techniques to literary works published on Instagram, Twitter, and TikTok. One of the findings indicates that the language style of Islamic literature has undergone structural simplification and increased the use of images, videos, and interactive features to more effectively capture the attention of a broader digital audience. In terms of meaning, there is a process of reinterpretation of Islamic values within contemporary contexts, reflecting adaptation to the social realities of media users. The function of Islamic literature has expanded beyond its traditional role, serving as a means of digital da'wah, informal education, and social critique. This study concludes that social media not only serves as a new space for disseminating Islamic literature but also as a platform for dialogue between tradition and modernity in contemporary Islamic cultural expression.